2017
DOI: 10.1108/intr-07-2016-0204
|View full text |Cite
|
Sign up to set email alerts
|

Does the Great Fire Wall cause self-censorship? The effects of perceived internet regulation and the justification of regulation

Abstract: Purpose The purpose of this paper is to examine the impact of internet censorship, which is represented by the Great Fire Wall, on Chinese internet users’ self-censorship. Design/methodology/approach A 3×2 factorial experiment (n=315) is designed. Different patterns of censorship (soft censorship, compared censorship, and hard censorship) and the justification of internet regulation are involved in the experiment as two factors. The dependent variable is self-censorship which is measured through the willingn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…For Xu et al (2008), in the context of e-commerce, at least, individuals' PA positively influences their disposition to value privacy. Zhong et al (2017) research identified a causal relationship between the Chinese government's internet censorship system and ordinary Chinese people's reactionsperceived internet censorship significantly decreases the willingness to discuss sensitive issues. Snowden (2015), when discussing in an online Q&A session on internet surveillance, stated, "The biggest change (caused by his leaking of sensitive government surveillance information) has been in awareness".…”
Section: Privacy Awarenessmentioning
confidence: 97%
“…For Xu et al (2008), in the context of e-commerce, at least, individuals' PA positively influences their disposition to value privacy. Zhong et al (2017) research identified a causal relationship between the Chinese government's internet censorship system and ordinary Chinese people's reactionsperceived internet censorship significantly decreases the willingness to discuss sensitive issues. Snowden (2015), when discussing in an online Q&A session on internet surveillance, stated, "The biggest change (caused by his leaking of sensitive government surveillance information) has been in awareness".…”
Section: Privacy Awarenessmentioning
confidence: 97%
“…The complexity of China also pertains to the high costs of civic engagement. Gradually, self-censorship has become common among Chinese people, which translated into their vigilance and reluctance to civic engagement (Zhong et al., 2017). Considering such contextual sophistication, the case of China offers the potential to further test the differential gains effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the citizen perspective, Indians are facing increasing uncertainty about the nature of civil liberties (Varshney, 2019). This may encourage individuals to use private social media and to make strategic decisions about what they report on public social media (Zhong et al, 2017).…”
Section: Social Media As Event Size Data In Indiamentioning
confidence: 99%